The Influence of The Physical Environment on The Quality of Life of Patients With Type 2 Diabetes Mellitus in The Belawan Health Center Area - Hartono, Hartono (Tadulako University, 2025)
Diabetes is one of the health problems, according to the International Diabetes Federation (IDF), Indonesia is the fifth country with the highest number of diabetes sufferers, namely 19.5 million people living with diabetes in 2021 and projected to increase to 28.6 million people in 2045 (IDF, 2024). In this study, researchers wanted to see the influence of the physical environment on the quality of life of Type 2 DM sufferers in the Belawan Health Center area. This study uses an analytical observational method with a cross-sectional design. The data used are primary and secondary data, where the population is 226 people. The sampling technique used by researchers is by using the Slovin formula, so the number of samples is 70 respondents. In this study, researchers found that Bedroom and Family Room Ventilation (p = 0.000; 0.005), Bedroom Humidity (p = 0.015), Bedroom and Family Room Ceiling Height (p = 0.001; 0.028), Bedroom and Family Room Lighting (p = 0.000; 0.001) have a significant relationship to the influence of the physical environment on the quality of life of Type 2 DM sufferers in the Belawan Health Center area. While Family Room Humidity (p = 0.085) does not have a significant relationship to the influence of the physical environment on the quality of life of Type 2 DM sufferers in the Belawan Health Center area. The most influential factors in this study were Bedroom Ventilation and Bedroom Lighting (p-0.000; 0.001 OR = 9.582; 3.727).